(untitled) (Altre Modernità, 2019)
This essay focuses on the challenges as well as the joys of reading postcolonial literary texts that are composed and printed in multiple, alternating languages. What postcolonial texts make manifest through their syntax, vocabulary, and style is the wide array of creative expression that the simultaneous presence of multiple languages makes available to the writer. A literary analysis able to appreciate this creative potential is in order if we want to go beyond an outdated understanding of literature and its forms. It is in fact in the act of reading that a lot of the disrespect surrounding postcolonial literature manifests itself. Caribbean literature marks an ideal place to start exploring the possibilities of a postcolonial literary analysis. A region “once deemed the antithesis of civilization” has become one of the most creative laboratories of verbal art, both written and oral, thanks to its radical creolization of the colonial languages. In the second part of my essay, I will present a model of literary analysis that uses as its crucial categories those coming from the traditionally disrespected language of the region: Creole.